Reality of the Arab elite intellectual from organic intellectual to Stressed intellectual - laib, rabiaa (Journal of Social Sciences and Humanities, 2025)
In the Arab world, as the waves of protests about the socio-economic and political conditions led by the Arab peoples increase in the Arab countries, the owners of which raise western anthem slogans, as they carry demands for justice and equality, and for the establishment of human rights principles in the Arab world; In the midst of the people's will to complete their destiny, the state of the Arab intellectual, who is determined to ask about his usefulness, his tasks and his effectiveness, especially when the Arab peoples were held responsible for the change. This is why the issue of this paper came about the crisis that still devastates the people of culture and awareness, in the Arab countries, or the class of leadership in society or what is known as sexual discrimination, especially after the peoples managed to distinguish between the intellectuals of the field and the intellectuals of books or academics, who were isolated from and kept away from their society. This was what I signed in A crisis that has lost its legitimacy and doubted its credibility before the public, so the article includes a group of goals, including what is essential and what is secondary. The fundamental objectives are to know the cultured, the tasks, the effectiveness and the consequences of this position between conscious and unconscious intellectuals. The second is to make this crisis a point of view and accountability, the aim of which is not only to define the position and role of the cultured in society, but also to reposition it as an actor in it.